Association of obesity with severity outcomes in hospitalized pediatric asthma exacerbations. (2nd January 2022) - Parlar-Chun, Raymond; Truong, Grace; Isbell, Tasia; Delgado, Yesenia; Arca, Makenna
Abstract: Introduction: While there seems to be an association between obesity and asthma, the exact nature of the relationship remains unknown. It is unclear if there is increased severity of exacerbation for those that require hospitalization. We examine the association between obesity and severity outcomes such as hospital length of stay, intensive care admissions, and need for continuous albuterol or magnesium administration. Methods: Patients 4 to 17 years old admitted between 1/1/2012–1/1/2016 with asthma identified by discharge codes were reviewed. Obesity was defined as BMI ≥95%. Clinical data such as age, gender, family history of asthma, use of controller medication along with outcome data such as length of stay, ICU admission, use of continuous albuterol, and use of magnesium were collected. Binary outcomes were analyzed with multivariate logistic regression while length of stay was analyzed with negative binomial regression. Results: Overall, 995 patients met inclusion criteria. The median age was 7 years old with 170 (17%) patients categorized as obese. We find no difference in length of stay (IRR 0.99 [0.91, 1.09], p  = 0.9), PICU admission (OR 0.72 [0.43, 1.21], p  = 0.22), or magnesium administration (OR 1.34 [0.95, 1.88], p  = 0.09) between obese and non-obese patients. There were increased odds of continuous albuterol use (OR 1.47 [1.02, 2.11]) for obese patients. Conclusion: We find no association between obesity and outcomes of length of stay, ICU admission, or magnesium administration. While growing evidence links obesity with asthma, our study suggests it may not be associated with the severity of exacerbation.